Expressions of Sovereignty: Law and Authority in the Making of the Overseas British Empire, 1576-1640 - MacMillan, Richard Kenneth (My University, 2001)
This thesis contributes to the body of literature that investigates the making of the British empire, circa 1576-1640. It argues that the crown was fundamentally involved in the establishment of sovereignty in overseas territories because of the contemporary concepts of empire, sovereignty, the royal prerogative, and intemationallaw. According to these precepts, Christian European rulers had absolute jurisdiction within their own territorial boundaries (internal sovereignty), and had certain obligations when it carne to their relations with other sovereign states (external sovereignty). The crown undertook these responsibilities through various "expressions of sovereignty". It employed writers who were knowledgeable in international law and European overseas activities, and used these interpretations to issue letters patent that demonstrated both continued royal authority over these territories and a desire to employ legal codes that would likely be approved by the international community. The crown also insisted on the erection of fortifications and approved of the publication of semiotically charged maps, each of which served the function of showing that the English had possession and effective control over the lands claimed in North and South America, the North Atlantic, and the East and West Indies. Finally, the crown engaged in diplomatic negotiations with other colonizing European powers, during which its envoys justified British overseas activities using an embryonic, common legal language in order to bring about the consensus of the international community. Because of the crown's expressions of internal and external sovereignty, this study concludes that the congeries of overseas territories ruled by Queen Elizabeth and the early Stuarts were -legally, structurally, and nominally, if not culturally, politically, and ideologically - an "empire". This conclusion challenges those of recent historians who have questioned both the crown's involvement in new found lands, and the efficacy of international law in the establishment of overseas sovereignty.
Keywords: History; History